(untitled) (Al-Qamar, 2021)
ʻAbdullāh IbnʻAbbās, one of the cousins of Holy Prophet Muhammad (ﷺ), is considered to be the greatest Mufassir of Quran. The Prophet had prayed a special prayer for him to understand the Quran. Due to his outstanding knowledge of Qur’ānic interpretation and traditions he won the title of Ḥibr al-Ummah (a great scholar and doctor of Muslim Ummah).The present article investigates the chains of Tafsīr on the authority of Ibn ʻAbbas, in terms of authenticity and weakness. Aim of this study is to link the Muslim Ummah with authentic traditions in order to eliminate the divisions among the Muslims. The study reveals that everything narrated on the authority of Ibn ʻAbbas or attributed to him in Tafsīr is not correct and accurate. The true accounts on the authority of Ibn ʻAbbas are five which are narrated on the authorities of Mujāhid Ibn Jabr, ʻAlī Ibn Abī Talḥah, ʻIkrimah, Atāʻ Ibn Abī Rabāh, and Saʻīd Ibn Jubayr, and the rest are among the weak, rejected or fabricated.